European banks and the Covid-19 crash test - Jézabel Couppey-Soubeyran; Erica Perego; Fabien Tripier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
European banks are stronger today than they were on the eve of the 2007-2008 financial crisis, thanks to the reforms that have taken place since then. But will they be strong enough in the face of a health crisis closer to the Great Depression of the 1930s than the stress-test scenarios envisaged by the European banking Authority for 2020? Access to central bank liquidity probably eliminates the risk of bank illiquidity, but it is not unthinkable that a bank insolvency crisis would have to be managed. The nonrepayment of one in five loans would be enough to exhaust the current level of capital. The resolution mechanism would then have to be mobilised, which is unlikely to be sufficient in a context where, according to the European Systemic Risk Board, the risk of simultaneous defaults is increasing sharply. It would then be possible to mobilise the European Stability mechanism. Should this instrument prove insufficient, the risk of the re-emergence of a sovereign debt crisis would increase.
Keywords: G21; G28; E58; 330; Money and Finance; Europe